Two lectures on the epistemic foundations of game theory - Giacomo Bonanno (University of California, Department of Economics, 2007)
This working paper contains the slides of two invited lectures on the Epistemic Foundations of Game Theory, delivered at the Royal Netherlands Academy of Arts and Sciences (KNAW) on February 8, 2007.
Keywords: 330